Engagement Mediates the Relationship Between Emotion and Achievement of Chinese EFL Learners - Feng, Enhao; Hong, Gang (Frontiers in Psychology, 2022)
Since the coming of Positive Psychology in the field of second language acquisition (SLA), the significance of emotion, especially positive emotion, has been well recognized by researchers. Educational research has indicated that both emotion and engagement play fundamental roles in learning process and psychological wellbeing, but research on their relationship is scant in SLA. The present study contributed to the development of Positive Psychology in SLA by investigating the relationships between achievement emotions, behavioral engagement, and self-reported English achievements. 633 students from four senior high schools in China participated in the study. Data collected through questionnaires revealed: (1) Participants reported a medium to high level of foreign language enjoyment (FLE), foreign language classroom anxiety (FLCA), and behavioral engagement; females had a higher level of FLE and behavioral engagement than males; the participants reported more anxiety and less enjoyment than western samples; (2) significant correlations were found between FLE, FLCA, behavioral engagement, and self-reported achievement; (3) significant mediating effects of behavioral engagement were found between both achievement emotions and self-reported achievement, and the mediating effect of engagement was stronger between FLCA and self-reported achievement. The findings extended the nomological network of achievement emotions, developed our insights into the complex relationships between emotions, learner engagement and language achievement, and revealed the mediating effects of behavioral engagement. Finally, directions for future study and implications for foreign language educators were provided.